Autonomic modulation and cardiac arrhythmias: old insights and novel strategies. Issue 11 (29th May 2021) - Chatterjee, Neal A; Singh, Jagmeet P
Abstract: The autonomic nervous system (ANS) plays a critical role in both health and states of cardiovascular disease. There has been a long-recognized role of the ANS in the pathogenesis of both atrial and ventricular arrhythmias (VAs). This historical understanding has been expanded in the context of evolving insights into the anatomy and physiology of the ANS, including dysfunction of the ANS in cardiovascular disease such as heart failure and myocardial infarction. An expanding armamentarium of therapeutic strategies—both invasive and non-invasive—have brought the potential of ANS modulation to contemporary clinical practice. Here, we summarize the integrative neuro-cardiac anatomy underlying the ANS, review the physiological rationale for autonomic modulation in atrial and VAs, highlight strategies for autonomic modulation, and finally frame future challenges and opportunities for ANS therapeutics.